PENGARUH MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA SEKRETARIAT DAERAH KABUPATEN KUTAI TIMUR - Rahayu, Krisnawati Wiji (EKONOMIA, 2017)
Influence Motivation Work To Performance Officer at the Secretariat of the East Kutai Regency is the extent to which the work motivation affects employee performance and employee willingness to devote the skills, knowledge, skills, energy and time in which the work motivation expect compensation from the company that can satisfy their needs.The formulation of the problem in this research is "Does Work Motivation significant effect on employee performance at the East Kutai Regency Secretariat?"The purpose of this research is to know and analyze the working motivation influence on employee performance in the East Kutai Regency Secretariat.The analysis tool in this research using descriptive analysis and simple linear regression analysis. In this study, the test is made freely (X = motivation) on the dependent variable (Y = performance of the employee). Testing the hypothesis can be stated as follows Ha: Motivation affect the performance of employees in the Secretariat of the East Kutai Regency, Ho: Motivation does not affect the performance of employees in the Secretariat of the East Kutai Regency, If: T hitung < T tabel then ho is received, the independent variable (motivation) is not effect on the dependent variable (employee performance) .T hitung > t tabel then ho is received, the independent variable (motivation) effect on the dependent variable (employee performance).The results of this research through a simple linear regression analysis test is that the variable X is motivation positive effect on employee performance due to variables has more than t table t count ie 4113 and Ttabel is 1,995.The hypothesis put forward in this study is that the motivational effect on the performance of employees in the Secretariat staff in the East Kutai Regency Thanks.